Differences in Pathological Composition Among Large Artery Occlusion Cerebral Thrombi, Valvular Heart Disease Atrial Thrombi and Carotid Endarterectomy Plaques - Liao, Yu; Guan, Min; Liang, Dan; Shi, Yingying; Liu, Jialin; Zeng, Xiuli; Huang, Shengming; Xie, Xiaomei; Yuan, Dingxin; Qiao, Hongyu; Huang, Li'an (Frontiers in Neurology, 2020)
Background and Purpose: Acute ischemic stroke (AIS) with large artery occlusion (LAO) may lead to severe disability or death if not promptly treated. To determine the source of cerebral artery occlusion thrombosis, we studied the pathological components of cerebral artery thrombosis with different etiological classifications to guide clinical formulation of preventive treatment. Materials and Methods: Eighty-eight thrombi from AIS patients with LAO, twelve atrial thrombi from patients with valvular heart disease (VHD), and eleven plaques obtained by carotid endarterectomy (CEA) from patients with carotid artery stenosis were included in this retrospective study. The hematoxylin and eosin–stained specimens were quantitatively analyzed for erythrocytes, white blood cells (WBCs) and fibrin; platelets were shown by immunohistochemistry for CD31. Results: The thrombi of VHD showed the highest percentage of fibrin, followed by those of cardioembolism (CE) and stroke of undetermined etiology (SUE), and these values were higher than those of the other groups. Plaques obtained by CEA showed the highest erythrocyte number, followed by the large artery atherosclerosis (LAA) thrombi, and showed significantly noticeable differences between other stroke subtypes. The proportions of fibrin and erythrocytes in the thrombi of CE and SUE were most similar to those in the thrombi of VHD, and the LAA thrombi were the closest to those obtained by CEA. CE thrombi and CEA plaques had a higher percentage of WBCs than thrombi of other stroke thrombus subtypes and VHD. Conclusions: CE and most cryptogenic thrombi may originate from the heart, and the formation of carotid atherosclerotic plaques may be related to atherosclerotic cerebral embolism. Inflammation may be involved in their formation.